2018
DOI: 10.1101/482349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-time markerless video tracking of body parts in mice using deep neural networks

Abstract: Markerless and accurate tracking of mouse movement is of interest to many biomedical, pharmaceutical, and behavioral science applications. The additional capability of tracking body parts in real-time with minimal latency opens up the possibility of manipulating motor feedback, allowing detailed explorations of the neural basis for behavioral control. Here we describe a system capable of tracking specific movements in mice at a frame rate of 30.3 Hz. To achieve these results, we adapt DeepLabCut – a robust mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…We use a recognition network to extract features from the analysis of single frames, that we base on the Xception 21 network architecture. We initialize parts of the network with ImageNet 4 weights. These features are then integrated over time by a TCN 22,23 to classify the behavior of the animal in each frame (see Methods for architecture and training details).…”
Section: Resultsmentioning
confidence: 99%
“…We use a recognition network to extract features from the analysis of single frames, that we base on the Xception 21 network architecture. We initialize parts of the network with ImageNet 4 weights. These features are then integrated over time by a TCN 22,23 to classify the behavior of the animal in each frame (see Methods for architecture and training details).…”
Section: Resultsmentioning
confidence: 99%
“…With the rapid development of computer vision and machine learning, object detection has welcomed its great progress and enabled us to automatically analyze videos, increasing the objectivity. For example, DeepLabCut has successfully achieved markerless feature extraction from pre-recorded videos (Mathis et al, 2018;Nath et al, 2019), and another group has demonstrated that the method has potential of being applied in real-time feedback control (Forys et al, 2018). DeepLabCut was built upon ResNet and not focused on the real-time detection.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still a challenge to solve complex problems, such as tracking similar objects near each other [23,24], especially under heavy background noise [18,23]. Using deep neural networks has provided significant contributions [25], but these approaches are still computationally expensive, hindering their widespread application [26]. Recent approaches to object tracking (e.g., hierarchical learned features for tracking and cognitive vision) present similar difficulties as algorithms and are limited to tracking only a few objects at the same time [27,28].…”
Section: Introductionmentioning
confidence: 99%